The new prognostic score for unresectable or recurrent gastric cancer treated with nivolumab: A multi‐institutional cohort study. Issue 6 (13th July 2021) - Sato, Sho; Oshima, Yoko; Matsumoto, Yu; Seto, Yasuyuki; Yamashita, Hiroharu; Hayano, Koichi; Kano, Masayuki; Ono, Hidetaka Andrew; Mitsumori, Norio; Fujisaki, Muneharu; Kunisaki, Chikara; Akiyama, Hirotoshi; et al.
Abstract: Background: Real‐world outcomes of nivolumab treatment for gastric cancer and associated prognostic factors remain unclear; the present study aimed to evaluate both items. Methods: A total of 278 consecutive patients treated with nivolumab for gastric cancer during 2017‐2019 were enrolled in this multi‐institutional retrospective cohort study. The impact of laboratory findings, immune‐related adverse events (irAEs), and clinicopathological factors on long‐term survival was evaluated using the Cox proportional hazards model. Results: The response rate was 11.7% in patients with measurable lesions. The overall and progression‐free survival estimates were 6.77 and 2.53 months, respectively. The incidence of irAEs was 30.6% (6.8% for grade ≥3). There were no treatment‐related deaths. Multivariate analysis revealed that C‐reactive protein level of ≤0.5 mg/dL (hazard ratio = 0.476, P  < .001), irAE occurrence (hazard ratio = 0.544, P  < .001), albumin level of >3.5 g/dL (hazard ratio = 0.688, P  = .045), performance status 0 (hazard ratio = 0.711, P  = .028), lymphocyte count >1000/μL (hazard ratio = 0.686, P  = .027), and differentiated histological type (hazard ratio = 0.740, P  = .046) were independently associated with improved survival. The median survival of patients with four or more good prognostic factors was 18.3 months. Conclusion: Nivolumab showed safety and survival benefits in patients with previously treated unresectable or recurrent gastric cancer. Low C‐reactive protein level, irAE occurrence, high albumin level, high lymphocyte count, and differentiated histological type may affect outcomes. The presence of four or more good prognostic factors may help identify likely long‐term survivors. Abstract : Multi‐institutional retrospective cohort study of nivolumab treatment for unresectable or recurrent gastric cancer revealed that the median overall and progression‐free survival estimates were 6.77 and 2.53 months, respectively. Low C‐reactive protein level, immune‐related adverse events, high albumin level, performance status 0, high lymphocyte count, and differentiated pathological type were associated with improved survival.